Psychological evaluation of candidates for the uterus transplantation French trial - Léa Karpel; Margaux Nicaise; Marie Carbonnel; Mathilde Le Marchand; Catherine Racowsky; Paul Pirtea; Jean‐Marc Ayoubi (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Since 2017, women with absolute uterine infertility due to Mayer‐Rokitansky‐Küster‐Hauser (MRKH) syndrome have been eligible to participate in a uterine transplantation clinical trial conducted by Foch Hospital in France. The aim of this study is to assess the psychological state of potential candidates, including recipients, their partners, and their living‐related donors. Material and Methods Sixteen potential uterus transplant candidates, including recipients, partners, and living‐related donors, participated in the study. The psychological evaluation of these candidates was conducted using three validated questionnaires: the Dyadic Adjustment Scale (DAS‐16), the Hospital Anxiety and Depression Scale (HADS), and the Fertility Quality of Life (FertiQoL) questionnaire. Results No depression symptoms were observed in any participant according to the HADS. Most recipients did not exhibit signs of anxiety; however, three partners and three donors reported moderate to high anxiety levels. A positive correlation was found between the recipient's psychological distress related to infertility (FertiQoL) and the anxiety scores of their donors. The emotional aspect of infertility was identified as the most distressing factor for the recipients. Conclusions While the overall psychological state of the participants was generally good, anxiety was notably present among donors and partners. Therefore, providing psychological support throughout the uterine transplantation process is essential for not only the recipients but also their partners and donors.